Career Development, Motivation, and Employee Performance at PT. Honda Makassar Indah Branch Jalan Gunung Bawakaraeng - Muhajji MS; Muh Rizal Halim; Muhammad Dedy Miswar (Journal of Entrepreneur, Business and Management, 2023)
The success of an agency from the past until now is still influenced by employee performance. The purpose of this study is to analyze the effect of career development and motivation partially or simultaneously on the performance of PT employees. Honda Makassar Beautiful Cab. Bawakaraeng Mountain Road. The results found that there was a positive and significant influence between career development and motivation on improving the performance of PT employees. Honda Makassar Indah Branch Jalan Gunung Bawakaraen either partially or simultaneously. Keywords: Performance, Career Development, Motivation